Consumer Innovation, e-Trust, and e-Loyalty: Evidence from the e-Commerce Industry in Aceh, Indonesia - Tengku Ahmad Helmi (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study looks at how consumer innovativeness affects e-trust and e-loyalty in the e-commerce setting in Aceh, Indonesia. It also examines whether e-trust plays a role in connecting consumer innovativeness with e-loyalty.Methodology: The research uses a quantitative approach and applies the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method to test the hypotheses. Data was gathered from 200 e-commerce users in Banda Aceh and Lhokseumawe through non-probability incidental sampling. The analysis was done using SmartPLS software to look at both direct and indirect links between the key variables.Findings: The findings reveal that consumer innovativeness exerts a positive influence on both e-trust and e-loyalty. Furthermore, e-trust significantly enhances consumer loyalty and acts as a mediating variable between innovativeness and loyalty. These results suggest that higher levels of innovativeness foster greater consumer confidence in e-commerce platforms, which, when supported by reliability and ethical practices, contribute to sustained customer engagement and loyalty.Conclusion: Consumer innovativeness and e-trust emerge as critical drivers of e-loyalty in Aceh’s e-commerce environment. Innovation fosters trust, and trust, in turn, builds long-term loyalty. The study highlights that innovation strategies should be both technologically progressive and culturally aligned with local values such as honesty, reliability, and ethical conduct to ensure sustainable consumer relationships.